Evaluating the effectiveness of the Czech national bank’s monetary policy: a longitudinal study since 1997 - Aliu, Florin; Rousek, Pavel; Nuhiu, Artor (Business, Management and Economics Engineering, 2025)
Purpose – This study examines the effectiveness of the Czech National Bank’s (CNB hereafter) monetary policy with a focus on its adaptive responses to macroeconomic indicators such as inflation, unemployment, economic growth, interbank rate, imports, exports, and exchange rates. The two-week repo rate served as the primary instrument for the analysis period from January 1997 to July 2023.Research methodology – The research employs a Vector Autoregression (VAR) model, complemented by Impulse Response Functions (IRF), Forecast Error Variance Decomposition (FEVD), Granger Causality and Johansen Cointegration Tests to analyse quarterly data on the dynamic interactions between the CNB’s two-week repo rate and key economic indicators.Findings – The research results show that the CNB monetary policies have mainly been effective in managing inflation targeting and sustaining economic stability. The considerable influence achieved through proactive policy adjustments to unemployment and interbank rates.Research limitations – External macroeconomic shocks not accounted for in the VAR model might influence the study results. Furthermore, the findings are specific exclusively to the Czech economy and may not be directly applicable to other countries with distinct economic structures or monetary policy frameworks.Practical implications – The research highlights the importance of predicting repo rate adjustments in response to changes in unemployment and interbank rates. CNB could use these findings to improve the understanding of policy changes and increase their effectiveness.Originality/Value – The findings offer valuable insights for policymakers, governments, and banking industry participants seeking to enhance monetary policy efficiency.